Watching Relationships Build over Time: A Video Analysis of a Hybrid Intergenerational Practice Program - Jennifer Kosiol; Gabriela Di Perna (Social Sciences, 2023)
Intergenerational programs are devoted to bringing older adults and children together because of their mutual benefits for both parties, such as reduction of ageism, relationship building, and shared learning. This intergenerational practice program included high school children and residents at an over-55 retirement village. The aim of this study was to develop an intergenerational shared learning program during COVID-19 using a hybrid model of face-to-face and videoconferencing technology. As a result of video analysis, researchers observed participant interactions and engagement during face-to-face and video conferencing sessions. The findings highlight the importance of a program structure that adapts to the changing environment and recognises that different settings (video and face-to-face) require different relationship-building activities. In addition, co-collaboration in the development of the program structure was essential to facilitate shared learnings.